Muslim women responding to globalization: Australian and Kenyan narratives - Samani, Shamim Ekbal (Curtin University, 2010)
The cultural determinism summoned in the discourse on the ‘war on terror’ embraces gender frames that invigorate the Islam and the West divide. In a vacuum of historical, geo-political and economic contexts, such frames conjure a Muslim woman archetype in opposition to Western conceptualizations of modernity. Ignoring the social milieu, as well as the current global transformations affecting people’s lives globally, conjectures in singular co-optations that isolate traits from religious dispositions have implications in how Muslim gender issues are perceived and addressed.This thesis intends to reconceptualize the Muslim woman image in an attempt to move beyond the gender polemics of cultural determinism and divide. Using narrative enquiry, the study makes a comparative analysis to discover how Muslim women in two disparate societies – Australia and Kenya are responding to the dynamics of change accelerated by globalization. Through primary research, it captures the narratives of 40 women along the axis of the two major influences on their lives - modernization and Islamization enhanced by globalization. In tracing the way global paradigms and policy changes at the macro-level have affected Muslim women and the responses produced, it provides an unconventional frame to view the lives of contemporary Muslim women.The study contends that in general, the issues facing Muslim women in the rapidly changing environment can be understood as challenges internal and external to faith orientation. On the one hand, the forces of a modern global culture offer opportunities and channels to redefine aspects of daily living and lifestyles. On the other, a resurgence of Islam manifests itself in an assertion of religious observance, cultural identity, values and morality that increasingly question these settings. The challenges are not confined to minorities in the West, but also borne by many in non-Western societies. Through its research findings, the study proposes that culture in itself is not immutable or a constant, but cultural expression is a vital part of utilizing opportunities availed by development and central to the process of development itself. As the means of comprehension without which life, lifestyles, objectives, aspirations and much more cannot be expressed, given meaning or be implemented, cultural expression is a vital aspect of human development. Accommodating these in the multicultural settings of contemporary environments is evermore salient in the globalized world.As the world becomes more interdependent, the challenges for a global society manifest in how societies organize themselves; how citizens participate and how decisions on collective issues can be more congruent to facilitate a more socially sustainable development. Through its schedule, the study attempts to provide an insight into the issues and challenges facing Muslim women in contemporary times and in the course of its findings makes a case for the value of diversity, cultural expression and a sustained representation of Muslim women within development issues.